Potensi Reduksi Sampah Domestik PT. X Surabaya Berdasarkan Komposisi Sampah - Brillyan Kusuma Pradani; Mohamad Mirwan; Muhammad Firdaus Kamal; Andrea Thrisiawan Pradhana (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Waste reduction efforts need to be made to reduce the burden of landfill in processing waste. The absence of a study on the potential for reducing domestic waste at PT X is an obstacle for the company to determine the right waste management scenario. PT X's waste management still adheres to the collection, transportation, and disposal system.  The test of this study is to analyze the potential waste reduction that can be done by PT X. This study was carried out by collecting waste transportation data and waste composition data obtained through the SNI 19-3964-1995 method. Waste transportation data will be reduced by waste composition data that has the potential to be used for kembai. The average waste transported to landfill is 6480 kg / month with the composition of waste dominated by 26.09% of food waste and plastic waste. Total waste that can be reduced by 52.07% by managing organic waste into compost and collecting and selling waste that still has a selling value. By carrying out this management, the average waste disposal of PT X can be reduced to 3374 kg / month.